Alexander Hamilton - Chernow, Ron. (New York : Penguin Press, 2004)
Traces the life of Alexander Hamilton, an illegitimate, largely self-taught orphan from the Caribbean who rose to become George Washington's aide-de-camp and the first Treasury Secretary of the United States.
Includes bibliographical references (p. [780]-788) and index.
Keywords: Hamilton, Alexander, -- 1757-1804.; Statesmen -- United States -- Biography; United States -- Politics and government -- 1783-1809.; Hamilton, Alexander, -- 1757-1804.; Political science; Statesmen; United States; 1783 - 1809; Biography